Implementasi Tata Tertib Sekolah Dalam Membentuk Kedisiplinan Siswa Sekolah Dasar Negeri 15 Mataram - Alfina; Arman Maulana; Muhammad Isra; Asrin (Primera Educatia Mandalika: Elementary Education Journal, 2025)
Discipline is a set of rules implemented to discipline students in schools. This study aims to demonstrate how school regulations play a role in shaping student discipline at Elementary School 15 Mataram. The method used in this research is a qualitative approach with a descriptive research type. Data collection was conducted through observations and interviews in the environment of SDN 15 Mataram. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The analysis results indicate that although the school has implemented regulations that must be adhered to by students, such as discipline in dressing, punctuality, and participation in religious activities like Dhuha prayers, only a portion of the students comply with these rules effectively. There are still students who show a lack of discipline in following the school regulations. This study emphasizes the importance of consistent implementation of school regulations to enhance student discipline, as well as the need for support from all parties, including parents and teachers, in creating a well-ordered and enjoyable learning environment.